2009
DOI: 10.1002/ca.20867
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the floor of the third ventricle in relation to endoscopic ventriculostomy

Abstract: Neuroanatomical structures that form the floor of the third ventricle (FTV) and neighboring tissues are important in the context of third ventriculostomy (TV) procedures. Thorough knowledge of the anatomical and histological organization of the region would be useful in understanding and preventing surgical complications. Taking the third ventricle region as a model, we aimed to simulate TV and make measurements of 23 cadaver brains, as well as perform histological examinations of the third ventricular floor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…In a previous study, MRI was performed after EVD insertion 22) , but this may distort the patient's original anatomy. As shown in a study by Aydin et al 1) , in most cases with ventriculomegaly the basilar artery gets closer to the third ventricle floor. This allows direct visualization of the pulsations of the basilar artery and its silhouette.…”
Section: Discussionmentioning
confidence: 81%
“…In a previous study, MRI was performed after EVD insertion 22) , but this may distort the patient's original anatomy. As shown in a study by Aydin et al 1) , in most cases with ventriculomegaly the basilar artery gets closer to the third ventricle floor. This allows direct visualization of the pulsations of the basilar artery and its silhouette.…”
Section: Discussionmentioning
confidence: 81%
“…Too anterior an entry point places the column of the fornix at risk for injury, while too posterior an entry point places structures such as the thalamostriate vein, venous angle, anterior caudate vein, superior choroidal vein, or anterior thalamus at risk. [1][2][3]5,6,8,10,[16][17][18]22,24,25 Our measurements allow the placement of the bur hole to be adjusted in relation to the coronal suture.…”
Section: Discussionmentioning
confidence: 99%
“…4 Traditionally, the coronal suture is used as an empirical landmark for this trajectory, with the bur hole placed in relation to it. 1 The coronal suture, however, does not course perpendicular to the midline. Instead, it projects anteriorly as it proceeds laterally from the sagittal suture.…”
mentioning
confidence: 99%
“…Aydin et al 2 found that the area between the infundibulum and mammillary bodies was composed of glial cells only, whereas the inner and outer surfaces of the third ventricle were covered with ependymal cells and arachnoidal cells, respectively. The stroma was composed of glial cells and was avascular.…”
Section: Discussionmentioning
confidence: 99%